Pendidikan Kewirausahaan, Ketrampilan, Dan Motivasi Serta Dampaknya Terhadap Minat Berwirausaha (Studi Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang) - Yongki Dwi Ardiansyah; Nur Hidayati; Eka Farida (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to determine entrepreneurship education, skills, and motivation and their impact on entrepreneurial interest in students at the Islamic University of Malang. The population in the study was 84 students or college students with the criteria of students who are still actively studying at the Faculty of Economics and Business. The technique used in this research is Multiple Linear Regression Analysis. Entrepreneurship education, skills, and motivation have a positive effect on the entrepreneurial interest of FEB UNISMA students. Entrepreneurship education partially affects the entrepreneurial interest of FEB UNISMA students. Skills have a partial effect on the entrepreneurial interest of FEB UNISMA students. Motivation has a partial effect on the entrepreneurial interest of FEB UNISMA students. Keywords : Entrepreneurship Education, Skills, Motivation, Interest In Entrepreneurship